Pemanfaatan internet untuk edukasi gizi bagi penyandang diabetes mellitus - Emyr Reisha Isaura; Probosuseno Probosuseno; Muhammad Primiaji Rialihanto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: The pattern of disease incidence has changed nowadays as indicated from epidemiological transition, from infection to noninfection diseases or noncommunicable diseases. The quantity of diabetes mellitus (DM) patients in Indonesia is increasing every year. Integrated management of DM requires synergy from different parties. According to Act No. 36/2009 on Health, article 17 paragraph 1 states that the government is responsible for the availability of access to information, education, and health facilities to improve and maintain highest health status.Objective: The study aimed to analyze the utilization of the internet or online media in the dissemination of recommended eating pattern and physical activities of DM patients as prevention against complication.Method: The study used cross-sectional design and was carried out in January 2013 at Surabaya Municipality. It used e-survey, with secondary data from hospitals at Surabaya Municipality. Samples were DM patients of 20-50 years old registered in hospitals and agreed with informed consent. Samples were taken purposively involving 66 respondents.Results: There was a difference in eating pattern among DM patients utilizing online and those using nononline media (OR=3.33; CI 95%=1.06-10.43; p=0.03); and in physical activities (OR=0.09; CI 95%=0.01-0.75; p=0.008).Conclusion: The utilization of online media affected eating pattern and physical activity pattern in DM patient as much as 3.33 times and 0.09 times greater than in those not using online media in looking for communication, information, and education resources in supporting prevention against DM complication. Thus online media could be one of the effective and efficient methods for the delivery of communication, information, and education for DM patients by health staff.